EDIMIOLOGICAL STUDY ON NATURE OF ASPHYXIAL DEATH ACROSS AGE RANGE AND GENDER IN SEMI-URBAN REGION OF HARYANA: AN EXPLORATORY COHORT STUDY - More, Rakesh; Kumar, Vijay; Dogra, Tirath Das; Kumari, Leena (Journal of Forensic Medicine and Toxicology, 2021)
This epidemiological study was conducted to differentiate the incidence of suicidal asphyxia death and homicidal asphyxia death in rural Haryana. It was also aimed to estimate the occurrence of asphyxia death across gender-wise and across various age categories. The retrospective study was performed among 226 medico legal cases reported for autopsy during 1st January 2016 to 30th June 2017 at two leading hospitals of Gurgaon, Haryana, using standard examination protocol. Based on descriptive analysis of the data, it was observed that hanging was the predominant mode of asphyxia. Incidence of asphyxia in males were nearly 28% higher than the females. Nonetheless, between 20 to 30 years contributed nearly 50% of the total cases of asphyxia. The findings of this study are alarming and concerning. Adequate socio personal and policy level intervention along with the awareness drive on mental health and stress management is warranted
Keywords: Asphyxia; epidemiology; hanging; ligature mark; Thyroid fracture